Solid Phase Extraction and Preconcentration of Copper(II) Using a Thia-crown-ether Modified Octadecyl Silica Membrane Disk - Mollaei, Kazem; Hossein Mashhadizadeh, Mohammad (Asian Journal of Chemistry, 2016)
A simple, rapid and cost effective preconcentration method is described for the determination of traces of copper in aqueous samples by flame atomic absorption spectrophotometry. The method is based on sorption of Cu2+ ion on octadecyl silica membrane disk modified with 3,6,9,14-tetrathiabicyclo[9.2.1]tetradeca-11,13-diene as a suitable neutral ionophore. The quantitative sorption of copper(II) ions is obtained on modified membrane disks by simply manipulating optimal conditions. The unique feature of the method is the quantitative recovery of analyte from membrane disk using thiourea solution. Effects of the various parameters such as reagent concentrations, sample volume, matrix, etc. on extraction of copper(II) ions have been investigated. Under optimized conditions, the relative standard deviation of the combined method of sample treatment, preconcentration and determination with FAAS (n = 10) is generally lower than 5%. The limit of detection (3s, n = 20) was 5 ng/mL. The method could easily be adopted by any laboratory as the inputs are minimal, inexpensive and easily available. The proposed method has been successfully applied for the determination of trace amount of copper(II) ion in water samples, ore and metallurgy products.